Fairytale ebook A novel. - Steel, Danielle (2017)
NEW YORK TIMES BESTSELLER • A wonderful, beautifully told tale from America’s favorite novelist,  Fairytale  is a captivating example of the truths that will always withstand even the darkest storms, and a reminder that sometimes fairytales do come true, and good prevails over evil in the end. Camille Lammenais has grown up in the beauty of the Napa Valley, surrounded by acres of her family’s vineyards. Her parents, Christophe and Joy, still deeply in love after two decades of marriage, have built a renowned winery and château modeled after Christophe’s ancient family estate in his native Bordeaux. Camille has had a perfect childhood, safe in her parents’ love. After graduating from Stanford, she returns to help manage Château Joy, her lifetime goal. But their fairytale ends suddenly with her mother’s death from cancer. Six months after losing his wife, the devastated Christophe is easy prey for a mysterious, charming Frenchwoman visiting the valley. The Countess de Pantin is the essence of Parisian seductiveness and sophistication. Within weeks they are a clandestine couple, making love like teenagers, glowing with their secret. Camille, still grieving for her mother, is shocked by the news that her father intends to remarry. Then she begins to see past the alluring looks, designer clothes, and elegant manners of the countess, while her innocent father is trapped in her web. When tragedy strikes again, Camille is at her stepmother’s mercy, and that of the two evil stepbrothers who appear. Camille needs to fight—first for her legacy, and then for her very life. But as she grapples with the plots being carried out against her, the countess’s elderly, kind, clever mother becomes her only ally, and a childhood friend emerges as a prince worthy of any fairytale.